STUDY OF SOIL POLLUTION WITH HEAVY METALS IN THE TOWN OF COPȘA MICĂ - MICLĂUȘU, Camelia; POP, Cristian; VÂLCAN, Bogdan; RADU, Anamaria; ROȘU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
Copşa Mică is known to be one of the most polluted towns in Romania because of the historical pollution generated by non-ferrous metallurgy. The purpose of this study is to investigate soil quality in urban areas, where land is sensitive and where the population is most exposed. Heavy metals (Pb, As, Cd, Cu, Zn) from the horizon of the surface soil were analyzed using descriptive statistical analysis, geostatistical analysis and pollution indices. The results of the analysis showed that the most affected areas of Copșa Mică are in S of the industrial platform in N-E of the town – in the Târnăvioara neighborhood and also in E-SE of neighborhood of the industrial platform. In areas with different land uses, the average concentrations of heavy metals have been decreasing in the following way: in public areas > in access areas (streets) > in yards > in gardens. The level of heavy metals in soil is influenced by anthropogenic activities in each functional area. The pollution load index (PLI) shows a level of soil pollution between moderate and very high. The biggest contribution through the single pollution index (PI) is represented in descending order by the following: Pb, Zn and Cd. There is no correlation between the calculated values of the PLI and the distance from the emission source (the metallurgical unit basket). Because a large area of land is affected by pollution, it is not feasible to apply greening measures, so interventions should be focused on decreasing the exposure of the population to heavy metals.